PERTANGGUNGJAWABAN PIDANA PELAKU TINDAK PIDANA MEMBUAT SURAT PALSU SEOLAH SURAT ASLI - Antonius; Fachri Bey (Reformasi Hukum Trisakti, 2022)
This research uses a legal-normative research method and the legal materials used in this research are primary legal materials consisting of criminal law books, court decision number 102/Pid.B/2020/PN Nga and also books as secondary legal materials, Circular Letter Number 04 of 2020, doctrine and an expert opinion. The results of the research illustrate that (1) the suspects were declared innocent because they did not fulfill all the elements contained in Article 263 paragraph (1) Jo. Article 55 paragraph (1) 1st of the Criminal Code. The suspect were found guilty in Article 268 paragraph (1) Jo. Article 55 paragraph (1) 1st of the Criminal Code. 2) The form of participation of the suspects based on Article 55 paragraph (1) of the Criminal Code, classified into members of the crime who took part in the act (medeplegen, mededader) together.